Pendekatan AD-LGI Dalam Edukasi Dan Pelatihan Pemanfaatan Daun Kelor Bagi Ibu Bekerja - Jayanti, Siswi; Astutik, Risa Septi; Denny, Hanifa M; Lestantyo, Daru; Suroto (Rena Cipta Mandiri, 2026)
Indonesia continues to face a high prevalence of stunting among children under five, while many women hold dual roles as workers and household food managers. This study aimed to evaluate the effectiveness of the AD-LGI approach in education and training on the use of moringa leaves for working mothers in Rowosari Village, Semarang City. A quasi-experimental one-group pretest–posttest design was applied to 44 mothers who were members of the community women’s group. The intervention included needs assessment, instructional design, education sessions, guided practice in cooking moringa-based dishes, and monitoring of home implementation. Knowledge about nutrition and the use of moringa leaves was measured before and after the intervention and analyzed with the Wilcoxon test. Total knowledge scores increased significantly (Z = -2.609; p = 0.009), with significant gains in understanding causes of nutritional problems (Z = -3.162; p = 0.002) and cooking methods for moringa (Z = -2.138; p = 0.033). The AD-LGI approach is concluded to be effective in improving the practical knowledge of working mothers and is potentially adaptable to community-based nutrition education programs using local foods.